Perubahan Kadar Vitamin Dan Mineral Pada Fermentasi Tempe Gude (Cajanus cajan L.) - Yuni Sine; Endang S Soetarto (Saintek Lahan Kering, 2018)
Tempeh is an Indonesian traditional food rich in vitamins and minerals easily digested by the body. Materials commonly used as tempe fermentation substrate are soybean (Glicyne max), but not all areas in Indonesia can be overgrown by soybeans, therefore it is needed alternative substrates for tempeh fermentation. Pigeon pea (Cajanus cajan L.) can be used as substrate of tempeh fermentation alternative by soybean, therefore it is needed alternative substrate for tempeh fermentation. this is because pigeon pea has a fairly good nutritional content and has the content of vitamins and minerals needed by the body. However, some of these minerals are bound to phytic acid compounds which are trypsin inhibitors, so the process of processing such as fermentation is one way to decompose phytic acid compounds. In this research has been done in the form of determination testing of ash, nitrogen, vitamin and mineral content by standard method, done before and after fermentation. Ash content decreased after fermentation, nitrogen content, iron content, calcium content and phosphorus content also decreased, while vitamin B12 has increased although not significant.